Nutrigenomics-Associated Impacts of Nutrients on Genes and Enzymes With Special Consideration of Aromatase - Jenzer, Helena; Sadeghi-Reeves, Leila (Frontiers in Nutrition, 2020)
Interactions are occurring in the course of liberation, absorption, distribution, metabolism, and excretion of active ingredients, or at the target receptors. They are causing therapy failures and undesirable events. Aromatase (syn. CYP19A1) is one of the specific CYP450 isoenzymes so far not elucidated in detail. As aromatase-inhibiting phytochemicals are currently recommended for breast cancer prevention and as add-on accompanying aromatase-inhibitor pharmacotherapy, it was the aim of this literature review to assess its genetic and -omics basis. Traditional antioxidation diet is one of the most approved explanations of inhibition of aromatase by flavonoid derivatives. Flavonoids compete for the oxygen provided by the heme moiety of aromatase in the course of aromatase-catalyzed conversion of steroid precursors to estrogens. A further explanation of flavonoids’ mechanism of action proposed is related to enzymatic histone deacetylation. By keeping DNA-structure wide through a high acetylation degree, acetylated histones favor transcription and replication. This mechanism corresponds to a procedure of switching genes on. Inhibiting acetylation and therefore switching genes off might be an important regulation of repressing cancer genes. Aromatase expression depends on the genotype and phenotype of a person as related to heme moiety encoded. Biosynthesis of porphyrins in turn depends on the substrates succinate and glycine, as well as on a series of further enzymes, with ALA synthetase as the rate-limiting step. It further depends on the absorption of iron depending on pH and redox state. Thus, to assess the function of aromatase precisely, multiple underlying biochemical pathways need to be evaluated. Genetic regulation of metabolism is a complex procedure requiring an understanding of multiple underlying pathways if personalized (nutritional) medicine should bring an advantage for a patient. Nutrition sciences need to consider the genome of an individual to truly find answers to nutrition-derived non-communicable diseases. With current GWAS (genome-wide association study) approaches, inherited errors of metabolism are precisely identified. Polygenic risks evaluation is much more difficult, but diagnostic tools are not yet available in a desired extent. The next step with profiling the exome and then the whole genome is on the threshold of becoming routine diagnosis and of bringing the desired details.